Infecção por neisseria gonorrhoeae em mulheres assintomáticas: revisão sistemática de literatura e estudo de prevalência em centro de referência em reprodução humana de Goiânia, Brasil - Fernandes, Liliam Borges (2013)
It is estimated that between 60 and 80 million people worldwide enfretem difficulties to reproduce at some point in their lives and it is estimated that this ratio reaches approximately 20% of couples of reproductive age. Gonorrhea is a common bacterial infection caused by Neisseria gonorrhoeae (NG), transmitted almost exclusively by sexual or perianal contact. In women genital infection can be asymptomatic and when it discovers there may be serious complications such as pelvic inflammatory disease, and ectopic pregnancy, a leading cause of female infertility. The molecular diagnostic techniques are powerful allies in the tracking of NG and other sexually transmitted diseases (STD). Therefore, an investigation was conducted in the scientific literature in the form of a Systematic Literature Review (SLR) on the prevalence of NG, molecular diagnostic techniques and the samples used in the detection of this bacterium. Simultaneously, we developed a chart review in the last 4 years to detect the prevalence of gonococcal infection among other diagnoses as the cause of infertility in women seen at the Laboratory of Human Reproduction - Clinical Hospital, Goiânia, Goiás. SLR was found in 720 articles of which 694 were excluded due to previously established criteria and 26 were included in this review. The population was predominantly young 7 (27%) and female sex workers 6 (23%). The age ranged from 12 to 59 years. The more frequent biological material was endocervical swab 10 (38.46%), vaginal swabs 8 (30.76%), urine 4 (15.38%) and the association of these 3 (11.53%). The in-house PCR was the choice of 12 trials for the diagnosis of NG. In the other 14 studies different commercial diagnostic kits were used. Gradually more it is observed the use of biological samples collected from a less invasive diagnosis of STD. Molecular techniques found in this study are the most used in asymptomatic patients, since they have greater efficiency in the detection of NG, whose gold standard applies only in symptomatic patients. In reviewing the records among the 340 women studied, the prevalence of NG 0.6% and co-infection with Chlamydia trachomatis (CT) was 0.6%. DIP was present in 2.1% of cases and 2 cases of coinfection of NG and CT and the mean age was 33 years. The CT and NG infections had low prevalence in the studied sample and studies are needed in other breeding centers in the country to confirm the prevalence of infections in this particular group of women with infertility problems.